MENGUBAH PARADIGMA DOSEN MENJADI PENDIDIK YANG UNGGUL DAN KAYA - Widi Winarso (Cakrawala - Jurnal Humaniora, 2012)
One of Indonesia's national development goals is to promote the general welfare and intellectuallife of the nation. The role of educating children in part imposed on the nation's educators, in thesense that here was a lecturer. While a professor himself could not produce the maximum outputprotege optimal if the welfare of less fulfilled. This paper tried to explore more deeply about thingsto do when a professor wants to improve their welfare. This journal writing method of writingbased on literature study, observations made and the author Based on the author's experiencewhile working in the finance department.Key word: Becoming Lecturers The Rich